RELASI LAKI-LAKI DAN PEREMPUAN (Menabrak Tafsir Teks, Menakar Realitas) - Achmad Mulyadi (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2009)
The term of gender has been perceived as man-womandifferentiation. The distinction is appeared due to culturalreality constructed by society. This concept is opposed to sex,which differentiate the terms of man-woman biologically.Thus, the difference in sex is a God construction, and cannotbe restudied. On the other hand, the difference in gender is asocial construction and it can be restudied (qabilun lin niqasy).Therefore, a gender concept on man-woman relation is alwaysdebatable in terms either in text study or in its reality contextin the society. This article elaborates the establishment of manwomanrelation from the text perspective, culturalconstruction and its reality today.